The Perceptions of Using Duolingo Application in Learning English for Student's Vocabulary Mastery - Fakhrurriana, Ria; Nisa, Aulia; Noni, Nurdin (Celebes Scholar pg, 2024)
The objective of this study was to investigate the attitudes around the use of the Duolingo program as a tool for enhancing students' vocabulary proficiency in the English language. The present study used a quantitative research methodology. The researcher administered a questionnaire to a group of students on their use of the Duolingo program. The participants in this research consisted of students enrolled in the English department at IAIN Kediri. The study sample consisted of 30 students that were enrolled in the English department. The findings indicate that 70% of respondents selected the option